Structural features affecting biomass enzymatic digestibility - Zhu, L.; O'Dwyer, J.P.; Chang, V.S.; Granda, C.B.; Holtzapple, M.T.
The rate and extent of enzymatic hydrolysis of lignocellulosic biomass highly depend on enzyme loadings, hydrolysis periods, and structural features resulting from pretreatments. Furthermore, the influence of one structural feature on biomass digestibility varies with the changes in enzyme loading, hydrolysis period and other structural features as well. In this paper, the effects of lignin content, acetyl content, and biomass crystallinity on the 1-, 6-, and 72-h digestibilities with various enzyme loadings were investigated. To eliminate the cross effects among structural features, selective pretreatment techniques were employed to vary one particular structural feature during a pretreatment, while the other two structural features remained unchanged. The digestibility results showed that lignin content and biomass crystallinity dominated digestibility whereas acetyl content had a lesser effect. Lignin removal greatly enhanced the ultimate hydrolysis extent. Crystallinity reduction, however, tremendously increased the initial hydrolysis rate and reduced the hydrolysis time or the amount of enzyme required to attain high digestibility. To some extent, the effects of structural features on digestibility were interrelated. At short hydrolysis periods, lignin content was not important to digestibility when crystallinity was low. Similarly, at long hydrolysis periods, crystallinity was not important to digestibility when lignin content was low.
Keywords: LIGNIN CONTENT; ACETYL CONTENT; CRYSTALLINITY; LIGNOCELLULOSIC BIOMASS; ENZYMATIC HYDROLYSIS